2019
DOI: 10.1002/ppul.24606
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing expiratory flows during mechanical cough in a pediatric neuromuscular lung model

Abstract: Mechanical insufflation‐exsufflation (MI‐E) is recommended for subjects of all ages with neuromuscular disorders (NMDs) and weak cough. There is a lack of knowledge on the optimal treatment settings for young children. This study aims to determine the MI‐E settings providing high expiratory airflow while using safe inspiratory volumes, and to identify possible limits where the benefit of incrementing the MI‐E settings to achieve a higher expiratory airflow, decreased. Using an MI‐E device and a lung model imit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
2
6
0
3
Order By: Relevance
“…The application of TFL during NIV treatment enabled us to adjust MI‐E settings directly, by titrating insufflation pressures and flow to the most optimal levels of laryngeal opening, partly alluded to in a previous model 6 . The procedure led to immediate changes in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The application of TFL during NIV treatment enabled us to adjust MI‐E settings directly, by titrating insufflation pressures and flow to the most optimal levels of laryngeal opening, partly alluded to in a previous model 6 . The procedure led to immediate changes in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative option is for the clinician to gain confidence with a more protocolized approach and once they have been successful, to individualize. Reasons for suggesting a more individualized approach include that bench [ 60 ] and clinical case series [ 57 , 59 ] have highlighted a greater negative to positive pressure that has been clinically effective. When it comes to the insufflation pressure, Mellis and Goebel [ 61 ] showed that it is not necessarily the deepest breath in that produces the highest CPF.…”
Section: Effective Mi-e Pressuresmentioning
confidence: 99%
“…86 Lachal et al 87 enhance our understanding of airflow dynamics, and a wide range of MI-E settings may be systematically applied to suggest possible combinations to be applied subsequently in patients. 52,88 The dogma that upper airway collapse during exsufflation causes MI-E treatment failure, highly influenced former evaluation methods, assessing the exsufflation phase alone. Sancho et al's CT-scannings 25 and Lacombe's flow-curve shapes 84 confirmed Bach's postulate that exsufflation caused upper airway collapse in subjects with bulbar dysfunction.…”
Section: Laryngeal Modelsmentioning
confidence: 99%
“…Increasing inspiratory time may be necessary to achieve required insufflation volume prior to exsufflation. 23,88,103 A prolonged inspiration seems to be physiological in inducing cough. 68 Several rapid MI-E cycles may be challenging or impossible to handle for individuals with bulbar dysfunction.…”
Section: Individualizing Mi-e Treatmentmentioning
confidence: 99%